Kontribusi Hukum Ekonomi Syariah dalam Pengembangan Industri Perbankan dan Keuangan Syariah - Zamzami; Tenda Budianto (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2023)
Islamic Economic Law has been a key driver in the development of Islamic banking and finance industries in various countries. With principles rooted in Islamic law, this industry offers financial solutions in line with religious values, avoiding prohibited practices of interest and speculation. Its contribution in expanding Islamic financial markets, enhancing financial inclusion, and providing more ethical investment alternatives is increasingly significant. This research discusses the positive impact of Islamic Economic Law on the growth of Islamic banking and finance industries, as well as the factors driving its success. The analysis employs a qualitative approach by examining relevant literature and case studies of Islamic banking industries in various countries. The findings indicate that the application of Islamic Economic Law principles stimulates product innovation, enhances consumer confidence, and provides financial system stability. Keywords: Islamic Economic Law, Islamic Banking Industry, Islamic Finance, Financial Inclusion, Islamic Principles.